Impact of generative artificial intelligence on the effectiveness of hyper-personalization of visual content in contemporary marketing strategies - Hneletska, Polina (Актуальні питання економічних наук, 2024)
The rapid pace of development of digital technologies and the growing role of data-driven decision-making underscore the relevance of studying the impact of generative artificial intelligence on the effectiveness of hype personalized visual content in modern marketing strategies. The purpose of the article is to substantiate the theoretical foundations and identify the features of the application of generative artificial intelligence to increase the effectiveness of hyperpersonalized visual communication in the modern marketing space. Methods used in the work: analysis of scientific literature – to study the current state of research on the issue; generalization and systematization – for a structured and complete presentation of the research results. Results. It is established that integrating generative artificial intelligence into marketing processes significantly increases the adaptability, scalability, and contextual relevance of visual content, thereby improving user engagement and conversion indicators. The technological principles and practical mechanisms for implementing generative models in marketing systems are considered, in particular, their role in automating content production and ensuring real-time personalization. It is emphasised that, despite significant advantages, the use of generative artificial intelligence is associated with several challenges, including reliance on data quality, ethical risks, transparency issues, and the potential impact of excessive personalization on consumer perception. The conclusions emphasize that generative artificial intelligence is a key driver of transformations in modern marketing, contributing to the transition to predictive and adaptive communication models, and that its effective application requires a balanced combination of technological innovations, ethical responsibility, and the strategic management of personalized content. Further scientific research should be directed toward developing methodological tools to assess the long-term effectiveness of artificial intelligence in hyperpersonalization processes, as well as toward an in-depth study of the ethical challenges and consequences of its use.